EMERGENCY CARE PROTOCOLS: CHALLENGES AND BEST PRACTICES IN BRAZILIAN NURSING - Candida de Oliveira, Valeria (Health and Society, 2026)
The Critical Role of Nursing in Brazil’s Emergency System Emergency care is a fundamental pillar of the Brazilian Unified Health System (SUS). Nursing professionals are the central workforce in the operation and management of these high-stakes services. This feature article provides an in-depth analysis of the emergency care protocols used in Brazilian nursing, examining the persistent challenges and the evidence-based best practices that are emerging from clinical practice and scientific literature. Our analysis, based on official documents from the Ministry of Health, resolutions from the Federal Nursing Council (COFEN), and relevant scientific articles, reveals a critical tension. While established protocols like the Manchester Triage System and the National Emergency Care Policy (PNAU) exist, their effective implementation is severely hampered by structural, organizational, and professional challenges. Key Obstacles Identified: Chronic overcrowding, Insufficient resources, High occupational stress, Low adherence to safety protocols. Conversely, best practices in areas such as mechanical ventilation, infection prevention, and patient safety offer clear pathways for improving care quality. The conclusion is clear: strengthening emergency nursing in Brazil requires overcoming systemic issues, investing in continuous professional training, and ensuring the consistent application of protocols for safer, more effective, and humanized care.